Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka di SD Unggulan Aisyiyah Yogyakarta - Anggraini Jamilatun; Waharjani Waharjani; Wantini Wantini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The emergence of a differentiated learning at Aisyiyah Superior Elementary School is motivated by the implementation of learning in elementary schools that has not shown effectiveness in appreciating the diversity and potential of students. The purpose of this study is to develop a differentiated learning model that is in accordance with the Independent Curriculum pattern and identify various factors that can affect the effectiveness of the implementation of the differentiated learning model in order to increase students' understanding material at Aisyiyah Superior Elementary School. This study uses a qualitative type of research. The results of this study develop a differentiated learning. Lessons by integrating the diversity and potential of students in the Independent Curriculum. Differentiated subjects with the Independent Curriculum pattern at Aisyiah Superior Elementary School Bantul went well, supported by adequate teacher preparation and training even though there were obstacles in understanding students' interests and talents properly. The implication is that this learning is able to accommodate various student potentials but also poses challenges for teachers in applying varied methods and switching from a teacher-centered to a student-centered approach.